Capital Market Reaction to the 2019 Indonesian Presidential Election in Advertising and Advertising Companies - Nabila Rizki Amalia; Latif Syaipudin (Demagogi: Journal of Social Sciences, Economics and Education, 2024)
The momentum of the 2019 Election had an impact on the capital market as a reaction to investors. Investors will of course pay attention to this momentum in the capital market to avoid losses. So by knowing the Average Abnormal Return value, investors will know how they should react to capital market movements during the 2019 Election. The aim of this research is to analyze the capital market reaction to the 2019 Presidential Election. The results of this research show that Average Abnormal Return occurs and has an impact on capital market reactions. This happens because capital market sentiment follows developments and changes regarding emerging issues regarding the winner in the 2019 Presidential Election. Basically, investors' main goal in purchasing shares is to gain profit, so the instability of the Average Abnormal Return will disrupt the process of investing in shares. due to a decline in investor confidence.